<meta http-equiv="refresh" content="1; url=/nojavascript/"> Sums and Differences of Rational Expressions with Unequal Denominators ( Read ) | Algebra | CK-12 Foundation
Dismiss
Skip Navigation
You are viewing an older version of this Concept. Go to the latest version.

Sums and Differences of Rational Expressions with Unequal Denominators

%
Best Score
Practice Sums and Differences of Rational Expressions with Unequal Denominators...
Practice
Best Score
%
Practice Now

Adding and Subtracting Rational Expressions with Unlike Denominators

One part of a line segment measures \frac{3}{x-2} . The other part of the segment measures \frac{2}{x+1} . What is the total length of the line segment?

Guidance

In the previous two concepts we have eased our way up to this one. Now we will add two rational expressions where were you will have to multiply both fractions by a constant in order to get the Lowest Common Denominator or LCD. Recall how to add fractions where the denominators are not the same.

\frac{4}{15} + \frac{5}{18}

Find the LCD. 15=3 \cdot 5 and 18=3 \cdot 6 . So, they have a common factor of 3. Anytime two denominators have a common factor, it only needs to be listed once in the LCD. The LCD is therefore 3 \cdot 5 \cdot 6=90 .

\frac{4}{15} + \frac{5}{18} &= \frac{4}{3 \cdot 5} + \frac{5}{3 \cdot 6} \\&= {\color{red}\frac{6}{6}} \cdot \frac{4}{3 \cdot 5} + \frac{5}{3 \cdot 6} \cdot {\color{blue}\frac{5}{5}} \\&= \frac{24}{90} + \frac{25}{90}\\&= \frac{49}{90}

We multiplied the first fraction by \frac{6}{6} to obtain 90 in the denominator. Recall that a number over itself is 6 \div 6=1 . Therefore, we haven’t changed the value of the fraction. We multiplied the second fraction by \frac{5}{5} . We will now apply this idea to rational expressions.

Example A

Add \frac{x+5}{x^2-3x} + \frac{3}{x^2+2x} .

Solution: First factor each denominator to find the LCD. The first denominator, factored, is x^2-3x=x(x-3) . The second denominator is x^2+2x=x(x+2) . Both denominators have and x , so we only need to list it once. The LCD is x(x-3)(x+2) .

\frac{x+5}{x^2-3x} + \frac{3}{x^2+2x} = \frac{x+5}{x(x-3)} + \frac{3}{x(x+2)}

Looking at the two denominators factored, we see that the first fraction needs to be multiplied by \frac{x+2}{x+2} and the second fraction needs to be multiplied by \frac{x+3}{x+3} .

&= {\color{red}\frac{x+2}{x+2}} \cdot \frac{x+5}{x{\color{blue}(x-3)}} + \frac{3}{x{\color{red}(x+2)}} \cdot {\color{blue}\frac{x-3}{x-3}} \\&= \frac{(x+2)(x+5)+3(x-3)}{x{\color{red}(x+2)} {\color{blue}(x-3)}}

At this point, we need to FOIL the first expression and distribute the 3 to the second. Lastly we need to combine like terms.

&= \frac{x^2+7x+10+3x-9}{x(x+2)(x-3)} \\&= \frac{x^2+10x+1}{x(x+2)(x-3)}

The quadratic in the numerator is not factorable, so we are done.

Example B

Add \frac{4}{x+6} + \frac{x-2}{3x+1} .

Solution: The denominators have no common factors, so the LCD will be (x+6)(3x+1) .

\frac{4}{x+6} + \frac{x-2}{3x+1} &= {\color{red}\frac{3x+1}{3x+1}} \cdot \frac{4}{{\color{blue}x+6}} + \frac{x-2}{{\color{red}3x+1}} \cdot {\color{blue}\frac{x+6}{x+6}} \\&= \frac{4(3x+1)}{{\color{red}(3x+1)}{\color{blue}(x+6)}} + \frac{(x-2)(x+6)}{{\color{red}(3x+1)} {\color{blue}(x+6)}} \\&= \frac{12x+4+x^2+4x-12}{{\color{red}(3x+1)} {\color{blue}(x+6)}} \\&= \frac{x^2+16x-8}{(3x+1)(x+6)}

Example C

Subtract \frac{x-1}{x^2+5x+4} - \frac{x+2}{2x^2+13x+20} .

Solution: To find the LCD, we need to factor the denominators.

x^2+5x+4 &= {\color{red}(x+1)} {\color{green}(x+4)} \\2x^2+13x+20 &= {\color{blue}(2x+5)} {\color{green}(x+4)} \\LCD &= {\color{red}(x+1)} {\color{blue}(2x+5)} {\color{green}(x+4)}

\frac{x-1}{x^2+5x+4} - \frac{x+2}{2x^2+13x+20} &= \frac{x-1}{{\color{red}(x+1)} {\color{green}(x+4)}} - \frac{x+2}{{\color{blue}(2x+5)}(x+4)} \\&= {\color{blue}\frac{2x+5}{2x+5}} \cdot \frac{x-1}{{\color{red}(x+1)}{\color{green}(x+4)}} - \frac{x+2}{{\color{blue}(2x+5)}{\color{green}(x+4)}} \cdot {\color{red}\frac{x+1}{x+1}} \\&= \frac{(2x+5)(x-1)-(x+2)(x+1)}{{\color{red}(x+1)}{\color{blue}(2x+5)}{\color{green}(x+4)}} \\&= \frac{2x^2+3x-5-(x^2+3x+2)}{(x+1)(2x+5)(x+4)} \\&= \frac{2x^2+3x-5-x^2-3x-2}{(x+1)(2x+5)(x+4)} \\&= \frac{x^2-7}{(x+1)(2x+5)(x+4)}

Intro Problem Revisit We need to add the two parts of the segment to get the whole.

\frac{3}{x-2} + \frac{2}{x+1}

The denominators have no common factors, so the LCD will be (x-2)(x+1) .

\frac{3}{x-2} + \frac{2}{x+1} &= {\color{red}\frac{x+1}{x+1}} \cdot \frac{3}{{\color{blue}x-2}} + \frac{2}{{\color{red}x+1}} \cdot {\color{blue}\frac{x-2}{x-2}} \\&= \frac{3(x+1)}{{\color{red}(x+1)}{\color{blue}(x-2)}} + \frac{(2)(x-2)}{{\color{red}(x+1)} {\color{blue}(x-2)}} \\&= \frac{3x+3+2x-4}{{\color{red}(x+1)} {\color{blue}(x-2)}} \\&= \frac{5x-1}{(x+1)(x-2)}

Therefore, the total length of the line segment is \frac{5x-1}{(x+1)(x-2)} .

Guided Practice

Perform the indicated operation.

1. \frac{3}{x^2-6x} + \frac{5-x}{2x-12}

2. \frac{x}{x^2+4x+4} - \frac{x-5}{x^2+5x+6}

3. \frac{2x}{x^2-x-20} + \frac{x^2-9}{x^2-1}

Answers

1. The LCD is 3x(x-6) .

\frac{3}{x^2-6x} + \frac{5-x}{2x-12} &= \frac{2}{2} \cdot \frac{3}{x(x-6)} + \frac{5-x}{2(x-6)} \cdot \frac{x}{x} \\&= \frac{6+x(5-x)}{2x(x-6)} \\&= \frac{6+5x-x^2}{2x(x-6)} \\&= \frac{-1(x^2-5x-6)}{2x(x-6)}

We pulled a -1 out of the numerator so we can factor it.

&= \frac{-1 \bcancel{(x-6)}(x+1)}{2x \bcancel{(x-6)}} \\&= \frac{-x-1}{2x}

2. The LCD is (x+2)(x+2)(x+3) .

\frac{x}{x^2+4x+4} - \frac{x-5}{x^2+5x+6} &= \frac{x+3}{x+3} \cdot \frac{x}{(x+2)(x+2)} - \frac{x-5}{(x+2)(x+3)} \cdot \frac{x+2}{x+2} \\&= \frac{x(x+3)-(x-5)(x+2)}{(x+2)(x+2)(x+3)} \\&= \frac{x^2+3x-(x^2-3x-10)}{(x+2)^2(x+3)} \\&= \frac{x^2+3x-x^2+3x+10}{(x+2)^2(x+3)} \\&= \frac{6x+10}{(x+2)^2(x+3)} \\&= \frac{2(3x+5)}{(x+2)^2(x+3)}

3. The LCD is (x-5)(x+4)(x+1)(x-1) .

\frac{2x}{x^2-x-20} + \frac{x^2-9}{x^2-1} &= \frac{(x+1)(x-1)}{(x+1)(x-1)} \cdot \frac{2x}{(x-5)(x+4)} + \frac{x^2-9}{(x+1)(x-1)} \cdot \frac{(x-5)(x+4)}{(x-5)(x+4)} \\&= \frac{2x(x+1)(x-1)+(x^2-9)(x-5)(x+4)}{(x-5)(x+4)(x+1)(x-1)} \\&= \frac{2x^3-2x+x^4-x^3-29x^2+9x+180}{(x-5)(x+4)(x+1)(x-1)} \\&= \frac{x^4+x^3-29x^2+7x+180}{(x-5)(x+4)(x+1)(x-1)}

Practice

Find the LCD.

  1. 3x, \ 7x
  2. x-2, \ 2x-1
  3. x^2 - 9, \ x^2-x-6
  4. 4x, \ x^2-6x
  5. x^2-4, \ x^2+4x+4, \ x^2+3x-10

Perform the indicated operation.

  1. \frac{5}{3x} + \frac{x}{2}
  2. \frac{x+1}{x^2} - \frac{5}{7x}
  3. \frac{x-5}{4x} + \frac{3}{x+2}
  4. \frac{5}{2x+6} + \frac{x-2}{x^2+2x-3}
  5. \frac{4x+3}{2x^2+11x-6} - \frac{3x-1}{2x^2-x}
  6. \frac{x}{3x^2+x-2} - \frac{2}{15x-10}
  7. \frac{3x}{x^2-3x-10} + \frac{x+1}{x^2-2x-15} - \frac{2}{x^2+5x+6}
  8. \frac{7+x}{x^2-2x} - \frac{x-6}{3x^2+5x} - \frac{x+4}{3x^2-x-10}
  9. \frac{3x+2}{x^2-1} - \frac{10x-7}{5x^2+5x} + \frac{3}{x-1}
  10. \frac{x+6}{2x-1} + \frac{2x}{3x+2} - \frac{5}{x}

Image Attributions

Reviews

Email Verified
Well done! You've successfully verified the email address .
OK
Please wait...
Please wait...

Original text